Phase stability and enhanced mechanical properties of nanocrystalline PVD CrCu coatings - Michael Burtscher; Christina Kainz; Paola Dorner; Simon Fellner; Velislava Terziyska; Markus Alfreider; Daniel Kiener (Journal of Materials Research and Technology)
The current work investigates the possibility of strengthening grain boundaries by nanoprecipitates using a CrCu coating model system. To this end, two compositions with 30 and 40 at.% of Cu and a balanced amount of Cr were synthesized via physical vapor deposition. The coatings exhibited a thickness of 1.8 μm and a Cr-based solid solution was determined for both systems in the as-deposited state. The precipitation of Cu upon annealing was determined via high-temperature X-ray diffraction analysis. Furthermore, nanoindentation measurements on heat-treated specimens showed a peak hardness and Young's modulus after 400 °C annealing for both coatings. Heating experiments in the transmission electron microscope verified the related formation of nano-scaled Cu precipitates. The conditional fracture toughness and resulting J-Integral were determined for the as-deposited and selected heat-treated states utilizing micromechanical notched cantilever experiments. The annihilation of microstructural defects and the precipitation of nm-sized Cu precipitates within and along the columnar Cr are regarded as the primary strengthening mechanisms. This statement is verified by the appearance of the individual fracture surfaces and proves that tailored precipitation of nm-sized Cu particles is a viable strategy to effectively boost the fracture mechanical properties of physical vapor-deposited CrCu alloys.